Identities, Youth and Belonging International Perspectives - Habib, Sadia; Ward, Michael R. M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book contains empirical research from established and emerging scholars who draw upon interdisciplinary perspectives of space and place in order to investigate young people's sense of identities and belongings in diverse international contexts. The contributors aim to enhance our understanding of how theories of belonging are employed in the study of youth identity as these young people come to belong at a local, national, global, and even virtual level. The collection draws on research in the rural, the urban, and online, showcasing key sites and communities that play a role in young people's lives as they negotiate their sense of agency and sense of identity within the contexts of the locale. Identities, Youth and Belonging will be of interest to students and scholars across a range of disciplines including sociology, education, social policy, politics and geography. .
1. Youth Negotiating Belonging in a Global World; Sadia Habib and Michael R. M. Ward -- 2. Growing Up in 'The Ends': Identity, Place and Belonging in an Urban East London Neighbourhood; Joy White -- 3. Young Indonesian Musicians, Upward Career Mobility and Feeling at Home; Oki Rahadianto Sutopo -- 4. Religion and (Re)negotiation of Belonging among Zimbabwean Migrant Youths in South Africa; Charles Dube -- 5. Being Kurdish at a Turkish University Campus: A Spatial Approach to Belonging; Baris Isci Pembeci -- 6. Transit and Transition: Student Identity and the Contested Landscape of Higher Education; Vicki Trowler -- 7. Using Bourdieu to Understand the Pathways to Belonging That Are Forged by Young Students of Refugee Experience in an Australian Mainstream School; Fiona Picton and Grant Banfield -- 8. Virtual Communities as Safe Spaces Created by Young Feminists: Identity, Mobility and Sense of Belonging; Raquel Miño-Puigcercós, Pablo Rivera-Vargas, and Cristóbal Cobo Romaní -- 9. Exploring the Potential for Community Where Diverse Individuals Belong; Kate J. Cassidy -- 10. (Un)Belonging in Higher Education: Negotiating Working-Class Masculinities Within and Beyond the University Campus Michael R. M. Ward -- 11. Portraits of Place: Critical Pedagogy in the Classroom; Sadia Habib -- 12. Conclusion: Young People Negotiating Belonging in Changing Times; Sadia Habib and Michael R. M. Ward.
Keywords: Sociology; Social groups; Emigration and immigration; Educational sociology; Sociology of Family, Youth and Aging; Human Migration; Sociology of Education